Analisa Daya Pembangkit Photovoltaic Array 9×10 WP Mendapat Efek Terbayang (Shading Effect) - Dwi Prima Putri Utami; Antonius Rajagukguk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The limitations of fossil energy resources in the future as an energy source for electricity generation and that’s effect on environmental pollution make the reason for the transition to renewable energy. Solar energy used in Photovoltaic (PV) systems can be an option for renewable energy generation sources. There are several problems that can interfere with the performance of large-scale PV. One that enhances PV performance is shading on a PV module, that make interferes PV performance. There is a decrease in current caused that problem, thereby reducing the output power of the PV system. This research studied about the effect of shading on the performance of large-scale PV systems through testing a 9 × 10 Wp miniature PV array and simulation using Matlab software. The use of diodes on a PV module can be done to prevent damage to the PV module due to shading. Through the power-voltage (P-V) and current-voltage (I-V) characteristic curves the effect of shading and the use of bypass and of this study note that the bypass diode and blocking diode output power generated by the PV module can be optimal.blocking diodes can be determined. Shading effect gaved in a decrease in power in the PV module. From the resultsKeywords: array, current, photovoltaic, power, voltage